NAVIGATING THE INTERSECTION OF DIGITAL TRANSFORMATION AND SUSTAINABLE BUSINESS STRATEGY IN EMERGING MARKETS: EVIDENCE FROM UZBEKISTAN - Khasanova Diyora; Sobiroba Makhsumabonu (TADQIQOTLAR, 2026)
Abstract The accelerating pace of digital transformation alongside the growing urgency of sustainability challenges has redefined the strategic priorities of modern organizations. This study investigates the integration of digital technologies and sustainable business practices in emerging markets, with a particular focus on Uzbekistan. By synthesizing existing literature and analyzing regional developments, the paper proposes a strategic framework for aligning digital innovation with environmental, social, and governance (ESG) objectives. The findings highlight that while emerging markets face infrastructural and institutional constraints, they possess unique opportunities to leapfrog traditional development stages through digital adoption. The study further emphasizes the critical role of business education in equipping future leaders with the competencies required to manage this transformation. The article contributes to both academic discourse and practical policymaking by offering insights relevant to managers, educators, and policymakers.